PE may be important in non‐shockable OHCA (Acute medicine & surgery, 2016)
BackgroundThe prognosis of non‐shockable out‐of‐hospital cardiac arrest is worse than that of shockable out‐of‐hospital cardiac arrest. We investigated the associations between the etiology and prognosis of non‐shockable out‐of‐hospital cardiac arrest patients who experienced the return of spontaneous circulation after arriving at hospital.Methods and ResultsAll subjects were extracted from the SOS‐KANTO 2012 study population. The subjects were 3,031 adults: (i) who had suffered out‐of‐hospital cardiac arrest, (ii) for whom there were no pre‐hospital data on ventricular fibrillation/pulseless ventricular tachycardia until arrival at hospital, (iii) who experienced the return of spontaneous circulation after arriving at hospital. We compared the patients' prognosis after 1 and 3 months between various etiological and presumed cardiac factors. The proportion of the favorable brain function patients that developed pulmonary embolism or incidental hypothermia was significantly higher than that of the patients with presumed cardiac factors (1 month, P < 0.0001 and P < 0.0001, respectively; 3 months, P = 0.0018 and P < 0.0001, respectively). In multiple logistic regression analysis, pulmonary embolism and incidental hypothermia were found to be significant independent prognostic factors for 1‐ and 3‐month survival and the favorable brain function rate.ConclusionsIn patients who suffer non‐shockable out‐of‐hospital cardiac arrest, but who experience the return of spontaneous circulation after arriving at hospital, the investigation and treatment of pulmonary embolism as a potential etiology may be important for improving post‐resuscitation prognosis.